Private Returns to Human Capital over Transition : A Case Study of Belarus - Francesco Pastore; Alina Verashchagina (Institute for the Study of Labor (IZA), 2004)
The gradualist approach to economic transition in Belarus would contribute to form the a priori expectation that the rate of return to education is low and the earnings profile by work experience flat, like they supposedly were under central-planning. However, the first available estimates of Mincerian earnings equations based on the Belarusian Household Survey on Incomes and Expenditure suggest that the skill payoff was high in 1996, at about 10.1% per year, and stable. The return to one year of work experience is also high at 5%. This result maintains also after controlling for sample selection bias, despite a general reduction in the annual rate of return to education by about 20-30%. Though, it is ambiguous whether the high-skill payoff is the consequence of market forces coming into play or of policy decisions, considering the pervasive role of the state in the process of wage determination.
Keywords: P52; J31; 330; educational economics; returns to human capital; economic transition; Belarus; Bildungsertrag; Humankapital; Übergangswirtschaft; Weissrussland